EXPLOITATION OF NATURE PORTRAYED IN THE SEA BEAST MOVIE - Veronika, Diah Ayu (Universitas Negeri Surabaya, 2024)
Nature has endowed humans with the resources humans need to continue their lives. However, excessive use of natural resources damages nature. For a long time, the issue of exploitation of natural resources and the negative impacts of exploitation of natural resources has been a frequently discussed topic. People who care about natural conditions often try to increase public awareness about protecting nature. One way to increase awareness of nature is through literary works. This study examines the depiction of nature exploitation in one form of literary work, namely movies. In this study, researcher used ‘The Sea Beast 2022’ movie as a research object. This used an ecocritical approach as a theory to analyze the exploitation of nature in ‘The Sea Beast’ 2022 movie. Apart from using ecocritical theory, the researcher also used a movie studies approach to analyze data. The results of this research show that there is exploitation of nature in the form of exploitation of wild animals depicted as sea beasts. Evidence of animal exploitation is that hunters use several weapons in hunting. Hunters use these weapons to paralyze sea beasts. Apart from that, hunters also disobey the principles of animal welfare. Apart from showing the existence of animal exploitation, in this study, the researchers also analyzed the main character's efforts to stop animal exploitation.